PENGELOLAAN ARSIP INAKTIF DI DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN SLEMAN - , AFRIANDA SETYAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final assignment report of inactive records management in Dinas Kebudayaan dan Pariwisata will talk about several aspect that related to managing an inactive records in records center. Any aspect included is exploration about inactive records condition, how to solve them, tools dan infrastructure availability, and some problem that appear in managing incative records. These concentration of inactive records management was still lack of textual records. Author make use of several methods to collect data in order to configure the final assignment report. The first method is indeepth interview. Second method is participation observation. And the last method is gather additional theories from library collection. With these 3 (three) methods, author will obtain a relevant data, that is appropriate with tittle of this report. In the last section of this report, author will provide a conclusion of this explanation about inactive records management. Based on the data, Dinas Kebudayaan dan Pariwisata has bring about inactive records management as good enough. Some problems arouse minimum quality of tools and infrastructure, lack of records manager, and lack of awareness in incative records management become a reason why records management canât be optimalized.